Froggy's day with Dad - London, Jonathan, 1947-; Remkiewicz, Frank (New York : Viking, 2004)
Froggy and his dad celebrate Father's Day with a game of miniature golf, among other things.
Horn Book.
School Library Journal.
2.1.
2.1
K-3
Keywords: Father's Day -- Fiction; Fathers and sons -- Fiction; Frogs -- Fiction; Miniature golf -- Fiction; Father-son relationship -- Fiction; Father's Day -- Fiction; Frogs -- Fiction; Miniature golf -- Fiction